University training and professional performance for public sector employees in library and information science - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2017)
The suitability of Library and Information Science undergraduate studies to jobs in Public Administration is reviewed. Tables and graphics that show the consequences of the current economic crisis on the employment rates of Public Administration are shown. Some final considerations about the relevance of the selection process that graduates must pass to access the different areas of Public Administration in Spain are given.
Keywords: Information professionals; Public service; Employment; Exams for public service; Education and training; Library and Information science.